НЕКОТОРЫЕ ОСОБЕННОСТИ СТРУКТУРНО-ФУНКЦИОНАЛЬНОГО СОСТОЯНИЯ ВЕНОЗНОЙ СИСТЕМЫ У БОЛЬНЫХ РЕВМАТОИДНЫМ АРТРИТОМ - А. В. Туев (Arhivʺ Vnutrennej Mediciny, 2014)
Surveyed 200 patients with rheumatoid arthritis (RA) in the age from 40 to 65 years. The main purpose of the work was the study of them features state of the vessels of the capacitive level of the circulatory system using the methods of plethysmography and dopplerography. The study presents the characteristics of structural and functional changes in the venous system in patients with RA. It was also noted that vein blood-flow in RA largely depends on the clinical characteristics of the arthritis, presence of concomitant arterial hypertension and structural changes of the venous wall.